Ensino-aprendizagem de LI em uma abordagem multimodal no Ensino Médio da Escola Pública - Almeida, Maria Helenice de Paiva (2015)
This research has as main objective to observe the English language teaching and learning in the contexts created in classroom activities in high school a State School, located in a suburb of a city in the state of São Paulo. Specifically the aim is to observe the use of multimodal texts in the English language classroom, so that we can have a vision of the role of multimodal text in English teaching, critical understanding (1) of the contexts built in class for the collective and cooperative-critical engagement of the participants, the construction and transformation of teacher and student roles; and 2) to investigate how the relationships built in the classroom contributed to the learning and development of the participants. The theoretical framework is based in the Theory of Socio-Historical-Cultural Activity (TASHC) with discussions of Vygotsky (1930, 1934), Leontiev (1977), and the most recent contributions of Engeström (2008, 2009) and Magalhães (2009, 2010) and Liberali (2009, 2010), among others discussing the formation of critical and creative students. The multimodal perspective in teaching is guided by the work of Cope and Kalantzis (2000), Rojo (2012), Kress and Leeuwen (2006). Methodologically, it is supported by the Critical Research Collaboration (PCCol), intervention research, discussed by Magalhães (2010) and other researchers as Liberali (2010), working with critical and reflective training of participants in research that propose not only understand the research context, but also to transform it. The focus is thus on the production of a research that promotes changes in current practices. Data were produced in English classes with students from 2nd. High School series, by recording audio and video classes the teacher-researcher and materials collected in the student's book and reference material proposed by SEESP. And analyzed from categories developed by Liberali (2013), Magalhães (2004 and 2009), Ninin (2013) and Kress and Van Leeuwen (2006). To understand the types of questions and student roles and teacher in quality of relations between participants to create teaching and learning environments for all participants. The results show that the development of collaborative critical context with the presence of multimodality in classes and Teaching Units for the teaching and learning of LI in this class enabled the construction of new student and teacher roles expanding the processing and performance opportunities in connection own